Evaluation Impact Traffic and Road Transport Policy in Reducing Accident Rates Vehicle Motorcycling In Indonesia - Aji Primanto; Linda Puspitasari (LPPM Universitas PGRI Sumatera Barat, 2024)
The problem Then traffic and transportation the way it happened started from a group public in A city start Lots use vehicle personal, where in a way direct user vehicle bear Lots cost like material burn and the time they use. Research This aiming For describe and analyze impact policy Constitution Number 22 of 2009 concerning Traffic and Road Transportation regarding level the accident that happened moment this, with amount increasing number of vehicles each year and capacity volume the path that is not Lots changed for ±13 years (2009-2022) since from issuance Constitution The results of the research show that with use method evaluation Where to measure the success of a policy's performance is by comparing before and after comparisons. The results of the evaluation before the enactment of Law Number 22 of 2009 concerning Traffic and Road Transportation Policy in the last five-year period (2003-2007) always showed a significant increase with fatality data. accident as many as 28,470 people. And after Law Number 22 of 2009 concerning Traffic and Road Transportation Policy and Plan National General Traffic and Road Transportation Safety (RUNK LLAJ) for 2010-2035 established and implemented for ± 13 years (2009-2022) by the Indonesian Government accident victims Then cross No show consistent results decrease but more leading to fluctuating conditions in which the amount reach 363,039 people.. Which is added with No achievement between the targets in 2022 is 1.37 % and its achievements by 1.71% like which has set in Plan National General Traffic Safety and Road Transport.